Systematic Literature Review (SLR): Gen Z Entrepreneurial Performance Based on Internal Factors - Puan Nabilla; Asmar Yulastri; Yuliana Yuliana (Jurnal Kewirausahaan dan Bisnis, 2025)
Indonesia as a developing country continues to encourage its economic growth through various sectors, one of which is entrepreneurship which is now largely driven by Generation Z. This generation has great potential in creating new businesses due to its proximity to technology, but still faces various internal obstacles such as low managerial skills, financial literacy, and readiness to face business risks. This research was conducted using a Systematic Literature Review (SLR) approach. The purpose of this study is to identify and synthesize internal factors that influence the entrepreneurial performance of Gen Z comprehensively as an effort to support entrepreneurship development. Research data was obtained from Scopus for the period 2015-2025. In addition, restrictions were also made with the keyword’s "entrepreneur" and "generation and Z" based on the initial search found 65 documents and only 63 documents were used as data sources and will be studied further. This study found that Gen Z's entrepreneurial performance is influenced by internal factors such as self-efficacy, motivation, digital skills, work experience, and values and mindset. Strengthening through educational practices, ecosystem support, and access to alternative funding is necessary for Gen Z to become innovative and socially impactful entrepreneurs.The conclusion of the study found that aspects of human resources include self-efficacy and courage to take risks, aspects of motivation and personal goals include intrinsic and extrinsic motivation, aspects of knowledge and skills consist of managerial and innovative skills; Personal experience aspects include previous work, internship, or business experience and value and mindset aspects include growth mindset, independence, and social innovation as dominant internal factors that influence the entrepreneurial performance of Generation Z.